Issues of Improving the Provisions of the Current Law of Ukraine Regarding the Prevention of the Origin and Spread of COVID-19 Coronavirus Disease (Law and Safety, 2020)
The author has studied the current state of the regulatory base on the prevention of the occurrence and spread of the COVID-19coronavirus disease in Ukraine and the practice of its application by authorized entities for the implementation of state policy in the field of health care and the protection of the rights and freedoms of citizens.The system of public administration in the field of ensuring the sanitary and epidemiological well-being of the population has been analyzed. The features of the distribution of powers of state agencies in this area after the liquidation of the State Sanitary and Epidemiological Service of Ukraine have been researched.The author concludes that the existing system of state agencies that carry out sanitary and epidemiological control in Ukraine requires further improvement by adopting a decree of the Government of Ukraine on the functioning of the State Sanitary and Epidemiological Service. The author of the article has also identified gaps in the current legislation of Ukraine on administrative offenses, which regulates the procedure for holding accountable for violation of sanitary and anti-epidemic rules. These shortcomings primarily relate to the content of the Code of Ukraine on Administrative Offenses, which contains the names of non-existent state agencies or their officials, the provisions of repealed laws or other by-laws.Based on the analysis of the laws of Ukraine and government decrees on the implementation of sanitary and anti-epidemiological measures, the author has formulated propositions aimed at regulating the legal status of the State Sanitary and Epidemiological Service; improvement of administrative proceedings in the field of health care and violation of quarantine rules; amending the list of agencies and officials authorized to consider cases of administrative offenses for the violation of sanitary rules; optimization of the mechanism of prosecution for failure to comply with legal orders of entities implementing the state sanitary and anti-epidemiological policy; expanding the list of powers of the National Police for the implementation of administrative detention, verification of documents and police custody within the sequestration.
Keywords: administrative responsibility; administrative offenses; National Police of Ukraine; coronavirus; sequestration; COVID-19